2019
DOI: 10.3389/fonc.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Signaling Regulates IL13Rα2 Expression to Promote Breast Cancer Metastasis

Abstract: Metastatic dissemination of cancer cells to distal organs is the major cause of death for patients suffering from the aggressive basal-like breast cancer (BLBC) subtype. Recently, we have shown that interleukin 13 receptor alpha 2 (IL13Rα2) is a critical gene that is overexpressed in a subset of BLBC primary tumors associated with poor distant metastasis-free survival (DMFS) and can promote extravasation and metastasis of breast cancer cells to the lungs. However, the upstream signaling mechanisms that promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Loss of E-cadherin represents a hallmark of EMT, which is frequently associated with increased cell invasion, and also contributes to activin A-induced invasion in breast cancer cells [54]. In a separate study, knockdown of activin A in breast cancer cells was shown to suppress migration in vitro and inhibit lung metastasis in vivo by inducing interleukin 13 receptor alpha 2 (IL13Rα2) overexpression [51].…”
Section: Activin a In Migration Invasion And Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of E-cadherin represents a hallmark of EMT, which is frequently associated with increased cell invasion, and also contributes to activin A-induced invasion in breast cancer cells [54]. In a separate study, knockdown of activin A in breast cancer cells was shown to suppress migration in vitro and inhibit lung metastasis in vivo by inducing interleukin 13 receptor alpha 2 (IL13Rα2) overexpression [51].…”
Section: Activin a In Migration Invasion And Metastasismentioning
confidence: 99%
“…While the response of normal and tumor cells to activin A with respect to cell growth is mixed, there is plenty of evidence that activin A stimulates cell migration in various cell types including some in which it inhibits proliferation like intestinal epithelial cells [49] and colon cancer cells [44]. In addition to migration, also invasion and metastasis were reported to be enhanced by activin A in several tumor entities including prostate [50] and breast cancer [51], oral squamous cell carcinoma [52] and MPM [20]. Enhancement of cell migration and invasion by activin A was linked to the activation of distinct signaling molecules.…”
Section: Activin a In Migration Invasion And Metastasismentioning
confidence: 99%
“…Five genes can be strongly linked to tumor relevant behavior and pathways. ACVR1B (also known as ALK4) is linked to tumorigenesis through its interaction with activin-A ( Kalli et al , 2019 ; Rautela et al , 2019 ). CASP10 inhibition leads to reduced apoptosis, while loss-of-function of RAP1A causes a reversion to a non-malignant phenotype in a model of invasive carcinoma ( Stammer et al , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a recombinant activin A promoted the proliferation of lung cancer cell lines SKLU1 and H460 and the invasion of ovarian cancer cell lines OCC1 and SKOV-3 without affecting proliferation (45). Recent evidence has implicated overactive activin signaling in breast cancer cell lines, including MCF7 and MDA-MB231, and higher levels of p-Smad2, p-Smad3 and activin A in advanced breast cancer (46,47). Activin A also promotes invasion, angiogenesis, epithelial-mesenchymal transition (EMT) and stemness in breast cancer cells (46).…”
Section: Critical Roles Of Activin In Tumorigenesismentioning
confidence: 99%